Peran Pengawasan Komisi Penyiaran Indonesia Aceh (KPIA) terhadap Iklan Obat-Obatan di Televisi Lokal - Yudha, Den Bagus Bima; Fazri, Anhar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the actions and role of supervision carried out by KPI Aceh regarding drug advertisements on local television. This is related to role theory, according to Bidle and Thomas, namely the problems that occur in broadcasting. This type of research is descriptive qualitative research. The results of this research found that there are four roles for KPI Aceh's supervision of television broadcasts, especially drug advertisements, namely as a detector of television broadcast content, as a selector, as an effector so that it is by P3SPS, as a communicator. KPI Aceh's supervisory role regarding drug advertisements on local television has also been carried out. In conclusion, there are four roles of KPI Aceh's supervision of the content of television broadcasts, especially drug advertisements, namely as a detector of the content of television broadcasts, as a selector of the content of television broadcasts, as an effector in changing behavior so that it is by P3SPS, as a communicator providing correct information regarding the content: television broadcasts, especially drug advertisements. Keywords: Broadcasting Supervision, KPI Aceh, Television, Drug advertising